Microbial load analysis in silicone gel breast implants - G.C.M. Santos; F.R. Lourenço; C.M.O. Amaral; I.S. Kikuchi; T.J.A Pinto (São Paulo State University (UNESP), 2010)
Silicone breast implants consist of biomaterials widely used in breast reconstitution surgeries or in mammary augmentation for esthetic reasons. A preliminary stage of the implant production process is vulcanization, which consists of heating the implant to 165±5°C for approximately 9 hours. The aim of this work was to evaluate the bioburden of silicone breast implants prior to the vulcanization process and the decline in bioburden due to this process, and to confirm the sterility of the gel contained in the membrane. Breast implant production stages were evaluated by microbial counting in different steps, according to the USP 32 methodology. To evaluation of decrease in microbial load, spores strips were introduced inside the implant, and after vulcanization cycles the strips were removed from the implant. The strips were transferred to tubes containing TSB, followed by incubation for 7 days at 30-35°C. The results obtained showed that the level of microbial contamination of gel implants is relatively low, and that vulcanization allowed for the inactivation of up to 108 spores. This study led us to the conclusion that vulcanization leaded to sterility of the gel inside the product. Thus, the final sterilizing process contributed to an increase in the Sterility Assurance Level.1.